PERAN KEPALA SEKOLAH DENGAN MENGGUNAKAN KEPEMIMPINAN TRANSFORMASIONAL DALAM UPAYA MENINGKATAN KUALITAS PEMBELAJARAN DI SMP NEGERI 1 GUMELAR KABUPATEN BANYUMAS TAHUN PELAJARAN 2014/2105 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study is aimed to determine: (1) The role of  principal by using transformational leadership in the effort to improve the  learning quality in SMP Negeri 1 Gumelar kabupaten Banyumas. (2) The learning quality of principal by using transformational leadership in the effort to improve the  learning quality in SMP Negeri 1 Gumelar kabupaten Banyumas. (3) Constraints principal roles by using transformational leadership in the effort to improve the learning quality in SMP Negeri 1 Gumelar kabupaten Banyumas.This study method uses descriptive qualitative research. The subjects of this are principal, vice-principal, teachers, staffs, and students. Data were collected through interviews, observation and documentation. The data  analysis tecnique uses an interactive model consisting of stages of data collection, data reduction, data presentation and conclusion.The results showed that the principal SMP Negeri 1 Gumelar in carrying out its role in improving the quality of learning in schools using transformational leadership has been good as well as the quality of teaching in the school does well also. As well as teaching and learning activities in SMP Negeri 1 Gumelar has been running smoothly. Application of transformational leadership principals are as follows: (1) The principal has a charismatic (idealized infleunce) to emulate the way the universe persistence with regard all creatures are the teachers and all the place is class. Teaching and learning activities run smoothly because everyone wants to learn with whoever and wherever place. (2) The principal is an inspiring figure (inspirational motivation) that can provide exemplary. So that subordinates will follow by itself so that teaching and learning activities running smoothly. (3) The principal has the intellectual stimulation (intellectual stimulation) is to make himself as an agent of the school development. With the development is done in all areas by the principal teaching and learning activities for the better. (4) The principal has individual consideration (individulized consideration) that can make effective teaching and learning activities. Principals can empower all subordinate capabilities. Constraints principals by using transformational leadership are as follows: (1) Constraints charismatic (idealized infleunce) is common misperception by subordinates in carrying out the task. (2) Constraints principals become inspirational figure (inspirational motivation) is no perfect man. (3) Constraints principal as intellectual stimulation (intellectual stimulation) is subordinate still maintain old traditions. (4) the principal obstacle in conducting individual pertimabangan (individulized consideration) is common misjudgment by the principal.